Perancangan Buku Komik Ludruk Berbasis Ilustrasi Digital Guna Mengenalkan Kembali Kesenian Tradisional kepada Remaja - Putri, Seila Ulfa Varadika; Budiardjo, Hardman; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
Ludruk art heritage of the ancestors, is the wealth of the local art and culture should be kept and preserved from extinction, a traditional theater arts that originated in East Java. Ludruk arts as an icon of Surabaya city already does not have the allure in the eyes of the youth, the development of technology and the rapid influx of television media making artistry Ludruk increasingly abandoned. Therefore, it is required a medium that can provide information about the arts, in order to re-introduce ludruk to teenagers. The method used was to create a comic book that gives information about art history include Ludruk Ludruk in Surabaya, Ludruk figures influential in Surabaya, the structure of the staging as well as presenting the paper and supported Ludruk media promotions such as keychains, bookmarks, stickers, x-banners, and posters. Through comic books is expected to increase the interest of teens against Arts Ludruk in Surabaya. Kata Kunci: Kesenian Ludruk, Ludruk Surabaya, Budaya Lokal, Buku Komik, Remaja.